PUBLIC ADMINISTRATION QUALITY AS INSURANCE OF POPULATION’S WELLBEING - Меlnychenko O.A. (Pressing Problems of Public Administration, 2017)
Further development of interpreting the notion of ‘public management’ has been provided. Interdependence between the level of the population’s wellbeing and public administration quality has been proved. Priority directions to improve the life of the population of Ukraine have been identi ed.